Administration of zoledronic acid alleviates osteoporosis in HIV patients by suppressing osteoclastogenesis via regulating RANKL expression - Lin, Wei (Mol Med, 2021)
BACKGROUND: Osteoporosis is a common phenomenon in HIV patients on tenofovir treatment, but its underlying mechanisms remain to be explored. METHODS: Quantitative real-time PCR was performed to analyze the expression of miR-302, miR-101, miR-145 and osteoclast-specific genes in the serum of HIV patients treated with tenofovir and ZOL. ELISA was used to evaluate the expression of RANKL, SMAD3 and PRKACB in the serum of these patients. Luciferase assay was carried out to explore the inhibitory effects of miR-302, miR-101 and miR-145 on the expression of PRKACB, RANKL and SMAD3, respectively. Western blot was used to examine the expression of genes involved in NF‑κB and JNK signaling pathways. RESULTS: ZOL treatment significantly suppressed the expression of CTx and osteocalcin in HIV patients treated with tenofovir. The BMD loss of HIV patients treated with tenofovir was effectively hindered by ZOL treatment. Mechanistically, the expression of miR-302, miR-101, miR-145, RANKL, SMAD3 and PRKACB in the serum was remarkably activated by ZOL treatment. Luciferase assays showed that miR-302, miR-101 and miR-145 effectively suppressed the expression of PRKACB, RANKL and SMAD3, respectively, through binding to their 3′ UTR. Furthermore, ZOL treatment notably restored the normal expression of osteoclast‑specific genes while activating NF‑κB and JNK signaling pathways. CONCLUSION: The findings of this study demonstrated that administration of ZOL suppressed the expression of RANKL via modulating signaling pathways of miR-101-3p/RANKL, miR-302/PRKACB/RANKL and miR-145/SMAD3/RANKL. Furthermore, down-regulated expression of RANKL by ZOL treatment alleviated osteoporosis in HIV-positive subjects treated with tenofovir.